2021
DOI: 10.3389/fnins.2021.611926
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Limb Amputees Adjust Quiet Stance in Response to Manipulations of Plantar Sensation

Abstract: Interfering with or temporarily eliminating foot-sole tactile sensations causes postural adjustments. Furthermore, individuals with impaired or missing foot-sole sensation, such as lower-limb amputees, exhibit greater postural instability than those with intact sensation. Our group has developed a method of providing tactile feedback sensations projected to the missing foot of lower-limb amputees via electrical peripheral nerve stimulation (PNS) using implanted nerve cuff electrodes. As a step toward effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Many ongoing efforts to restore locomotion for persons with leg amputation involve motor intent classification strategies based on electromyography (EMG) and intrinsic prosthetic signals 5 , 6 . However, in the absence of visual feedback, postural responses and balance during walking remain challenging for persons with leg amputation 7 , 8 , which may indicate that motor control and proprioceptive percepts are significantly altered in persons that have undergone a conventional amputation procedure 9 11 . Toward better, more biomimetic control of an external prosthesis, invasive nerve interfacing using artificial electrical stimulation has shown great potential in restoring cutaneous 12 14 and proprioceptive sensation 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many ongoing efforts to restore locomotion for persons with leg amputation involve motor intent classification strategies based on electromyography (EMG) and intrinsic prosthetic signals 5 , 6 . However, in the absence of visual feedback, postural responses and balance during walking remain challenging for persons with leg amputation 7 , 8 , which may indicate that motor control and proprioceptive percepts are significantly altered in persons that have undergone a conventional amputation procedure 9 11 . Toward better, more biomimetic control of an external prosthesis, invasive nerve interfacing using artificial electrical stimulation has shown great potential in restoring cutaneous 12 14 and proprioceptive sensation 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the absence of visual feedback, postural responses and balance during walking remain challenging for persons with leg amputation 7 , 8 , which may indicate that motor control and proprioceptive percepts are significantly altered in persons that have undergone a conventional amputation procedure 9 11 . Toward better, more biomimetic control of an external prosthesis, invasive nerve interfacing using artificial electrical stimulation has shown great potential in restoring cutaneous 12 14 and proprioceptive sensation 11 , 12 . However, due to the complexity of afferent signaling through artificial nerve stimulation, and the relatively limited resolution of state-of-the-art implantable devices, it can be challenging to engineer stable neuroprosthetic interfaces that offer natural cutaneous and proprioceptive percepts.…”
Section: Introductionmentioning
confidence: 99%
“…Though the participant had previously utilized the SNP in a laboratory context and performed tasks including motor imagery, postural stability ( Shell et al, 2021 ), treadmill walking, and walking overground ( Christie et al, 2020 ), the emergence of automatic strategies to specifically gather sensory information, such as toe tapping and rocking on the prosthesis, only occurred after several months of daily use of the SNP. The implication is that in lab training alone may not be sufficient for motor learning to reach the level of automaticity, and thus daily at-home training may be required.…”
Section: Discussionmentioning
confidence: 99%
“…LLA01 received the surgically implanted SNP 7 years before the time of this report, with consistent operation and stable sensory responses throughout. The data collection for this study lasted for approximately 5 months, during which time participants routinely visited our laboratory for other experiments after their implant surgery ( 13 , 15 , 18 , 60 , 61 ). Throughout this and other previously reported studies, the implanted composite flat interface nerve cuff electrodes (C-FINEs) have demonstrated stable and reliable performance, as evidenced by eliciting sensations in consistent locations related to the plantar surface of the foot of the missing limb.…”
Section: Discussionmentioning
confidence: 99%